Estimation of the net production of moss community at Langhovde, East Antarctica - Yoshio Ino (National Institute of Polar Research, 1992)
Field measurements of net photosynthesis and dark respiration (CO_2 exchange) of moss colonies were carried out at Langhovde, East Antarctica from 9 to 17 January 1988. Each colony growing at the Yukidori Valley, Langhovde was composed of Grimmia lawiana, Bryum pseudotriquetrum or the mixture of Ceratodon purpureus and B. pseudotriquetrum. Microclimatic data (photosynthetic photon flux density and moss temperature) in the assimilation chamber were recorded at the same time. A simple model to estimate the net photosynthetic rate and dark respiration rate on the basis of the microclimatic data was developed on KAPPEN'S model (KAPPEN et al. : Polar Biol., 9,415 1988). Net primary production of these moss colonies was calculated with the microclimatic data recorded separately at the Yukidori Valley from January 1988 to January 1989 (OHTANI et al. : JARE Data Rep., 152,1990). The estimated net production rates of moss colonies growing in the upper reaches of the Yukidori Valley ranged from 8.8 to 11.3 mol CO_2m^・y^, or from 230 to 296 gdw m^・y^.